Cloning and Molecular Analysis of the Poly(3-hydroxybutyrate) and Poly(3-hydroxybutyrate-co-3-hydroxyalkanoate) Biosynthesis Genes in Pseudomonas sp. Strain 61-3 - Matsusaki, Hiromi (American Society for Microbiology, 1998)
Two types of polyhydroxyalkanoate (PHA) biosynthesis gene loci (phb and pha) of Pseudomonas sp. strain 61-3, which produces a blend of poly(3-hydroxybutyrate) [P(3HB)] homopolymer and a random copolymer {poly(3-hydroxybutyrate-co-3-hydroxyalkanoate) [P(3HB-co-3HA]} consisting of 3HA units of 4 to 12 carbon atoms, were cloned and analyzed at the molecular level. In the phb locus, three open reading frames encoding polyhydroxybutyrate (PHB) synthase (PhbC(Ps)), β-ketothiolase (PhbA(Ps)), and NADPH-dependent acetoacetyl coenzyme A reductase (PhbB(Ps)) were found. The genetic organization showed a putative promoter region, followed by phbB(Ps)-phbA(Ps)-phbC(Ps). Upstream from phbB(Ps) was found the phbR(Ps) gene, which exhibits significant similarity to members of the AraC/XylS family of transcriptional activators. The phbR(Ps) gene was found to be transcribed in the opposite direction from the three structural genes. Cloning of phbR(Ps) in a relatively high-copy vector in Pseudomonas sp. strain 61-3 elevated the levels of β-galactosidase activity from a transcriptional phb promoter-lacZ fusion and also enhanced the 3HB fraction in the polyesters synthesized by this strain, suggesting that PhbR(Ps) is a positive regulatory protein controlling the transcription of phbBAC(Ps) in this bacterium. In the pha locus, two genes encoding PHA synthases (PhaC1(Ps) and PhaC2(Ps)) were flanked by a PHA depolymerase gene (phaZ(Ps)), and two adjacent open reading frames (ORF1 and phaD(Ps)), and the gene order was ORF1, phaC1(Ps), phaZ(Ps), phaC2(Ps), and phaD(Ps). Heterologous expression of the cloned fragments in PHA-negative mutants of Pseudomonas putida and Ralstonia eutropha revealed that PHB synthase and two PHA synthases of Pseudomonas sp. strain 61-3 were specific for short chain length and both short and medium chain length 3HA units, respectively.